2009
DOI: 10.31729/jnma.222
|View full text |Cite
|
Sign up to set email alerts
|

Need for Improvement of Medical Records

Abstract: Introduction: A medical record is a systematic documentation of a patient’s medical history and care for legal and future use. A poor quality medical record can negatively affect patient care and safety. The study aims to assess the adequacy of medical records in Bir Hospital, a central hospital.Methods:A cross-sectional study was conducted by analyzing consecutive discharge summaries of patients admitted during a 6 month period in a single unit of a tertiary care center. The discharge summary format of the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…To improve patient care and safety as well as working conditions for doctors, the current deficits in teaching, discussion and research on this topic must be addressed [13]. Improving the systematic teaching of how to write DS is within the responsibility of the medical schools, specialty training institutions and professional bodies [32,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To improve patient care and safety as well as working conditions for doctors, the current deficits in teaching, discussion and research on this topic must be addressed [13]. Improving the systematic teaching of how to write DS is within the responsibility of the medical schools, specialty training institutions and professional bodies [32,36].…”
Section: Discussionmentioning
confidence: 99%
“…Despite this effort, DS often have considerable shortcomings regarding their completeness and quality [6,7], which is especially true for the prescription of medications [8]. Studies have consistently shown that, at most, only 70% of the DS meet the requirements established in the guidelines, and up to 40% are incorrect in some way [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Another possible explanation, although less likely, was the possibility of inadequate patient management documentation, including prophylactic antibiotic administration, in the medical record. Despite the significant improvement in medical data recording, inaccurate and incomplete medical records remain a worldwide problem [ 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Access to both discharge instructions and radiology reports would be possible with the discharge module, as opposed to a paper-based discharge summary that a patient is supposed to take to their follow-up ambulatory visit. Discharge summaries are often unavailable or incomplete in many cases [21][22][23][24]. Furthermore, radiology reports are likely to not be included in the printed summaries.…”
Section: Discussionmentioning
confidence: 99%